2021
DOI: 10.3390/vaccines9090981
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 COVID-19 Vaccine Hesitancy among Parents of 4023 Young Adolescents (12–15 Years) in Qatar

Abstract: Parental vaccine hesitancy (VH) remains a barrier to full population inoculation, hence herd immunity against the SARS-CoV-2 virus. We aimed to determine parental VH rate, subgroups and influencing factors related to the BNT162b2 COVID-19 vaccine among their young adolescents (12–15 years old) in Qatar. A retrospective, cross-sectional study was conducted from 17 May to 3 June using vaccination booking records of 4023 young adolescents. Sociodemographic characteristics (i.e., age, sex, and nationality), health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 46 publications
6
59
0
2
Order By: Relevance
“… Yes [Y], unsure [U], no [N] Yes: 50.0 Unsure: NR No: NR ( Lackner and Wang, 2021 ) If a vaccine against COVID-19 is available, how likely would you be to get your children vaccinated? A scale from 1 to 100 Yes: NR Unsure: NR No: NR ( Musa et al, 2021 ) Parents' agreement to obtain a confirmed COVID-19 vaccine booking appointment for their children at the time of study Yes [Y], no [N] Yes: 82.1 No: 17.9 ( Temsah et al, 2021 ) Are you willing/intending to give the COVID-19 vaccine to your child (children)? Yes [Y], unsure [U], no [N] Yes: 47.5 Unsure: 20.5 No: 32.0 ( Urrunaga-Pastor et al, 2021 ) Will you choose to get a COVID-19 vaccine for your child or children when they are eligible?…”
Section: Resultsmentioning
confidence: 99%
“… Yes [Y], unsure [U], no [N] Yes: 50.0 Unsure: NR No: NR ( Lackner and Wang, 2021 ) If a vaccine against COVID-19 is available, how likely would you be to get your children vaccinated? A scale from 1 to 100 Yes: NR Unsure: NR No: NR ( Musa et al, 2021 ) Parents' agreement to obtain a confirmed COVID-19 vaccine booking appointment for their children at the time of study Yes [Y], no [N] Yes: 82.1 No: 17.9 ( Temsah et al, 2021 ) Are you willing/intending to give the COVID-19 vaccine to your child (children)? Yes [Y], unsure [U], no [N] Yes: 47.5 Unsure: 20.5 No: 32.0 ( Urrunaga-Pastor et al, 2021 ) Will you choose to get a COVID-19 vaccine for your child or children when they are eligible?…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52][53][54] We believe to date there have been limited studies assessing vaccine hesitancy in the United Arab Emirates (UAE) although there have been concerns with high rates of vaccine hesitancy among the population in Arab countries as well as among parents of young adults. 23,[55][56][57] However, this is not universal. [58][59][60] Consequently, our aim was to evaluate the acceptance of the COVID-19 vaccination and the related factors among university students in UAE.…”
Section: Introductionmentioning
confidence: 99%
“…Effective vaccines against SARS-CoV-2 infection, which are commonly considered as one of the most successful ways to prevent and control the disease [ 19 ], are currently available for all adults in Russia. However, vaccine hesitancy, especially in younger age groups, remains a significant barrier to overcome in achieving effective herd immunity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%